2021
DOI: 10.3390/plants10081505
|View full text |Cite
|
Sign up to set email alerts
|

The Remarkable Journey of a Weed: Biology and Management of Annual Ryegrass (Lolium rigidum) in Conservation Cropping Systems of Australia

Abstract: Annual ryegrass (Lolium rigidum Gaud.), traditionally utilised as a pasture species, has become the most problematic and difficult-to-control weed across grain production regions in Australia. Annual ryegrass has been favoured by the adoption of conservation tillage systems due to its genetic diversity, prolific seed production, widespread dispersal, flexible germination requirements and competitive growth habit. The widespread evolution of herbicide resistance in annual ryegrass has made its management within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 121 publications
(191 reference statements)
1
20
0
Order By: Relevance
“…The development of new herbicides that are effective against L. rigidum , particularly those with a reduced propensity to generate resistance, is of the highest priority given the economic impact of this species. An overreliance on a small number of herbicide modes of action has culminated in the widespread evolution of multiple resistance mechanisms in L. rigidum ( Bajwa et al, 2021 ; Owen et al, 2014 ). In Australia alone, herbicide-resistant L. rigidum invades 8 million hectares of cropping land, resulting in revenue losses of AUD$93 million annually ( Llewellyn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new herbicides that are effective against L. rigidum , particularly those with a reduced propensity to generate resistance, is of the highest priority given the economic impact of this species. An overreliance on a small number of herbicide modes of action has culminated in the widespread evolution of multiple resistance mechanisms in L. rigidum ( Bajwa et al, 2021 ; Owen et al, 2014 ). In Australia alone, herbicide-resistant L. rigidum invades 8 million hectares of cropping land, resulting in revenue losses of AUD$93 million annually ( Llewellyn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Static docking and biochemical assays revealed that in contrast to the allosteric binding of these inhibitors to DHDPS, active site binding is responsible for their inhibition of DHDPR. Additionally, we extended our previous in vivo activity studies on A. thaliana to include one of the most agriculturally problematic weeds in the world, rigid ryegrass ( Lolium rigidum ) ( Bajwa et al, 2021 ; Busi and Beckie, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, as the above results show, both species are effectively 100% outcrossing. However, one key life-history difference is that R. raphanistrum displays prolonged seed longevity in the soil compared to L. rigidum (Bajwa et al, 2021). As our general results above show, prolonged seed dormancy is likely to significantly delay the rate at which drive will occur.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the development of annual ryegrass resistance to multiple herbicide families, including that of glyphosate, has proven to be a major problem facing Australian producers [9,10]. Resistant annual ryegrass can be exceptionally difficult to control, and its management has direct ramifications for the successful production of cereal crops, particularly in Western Australia and New South Wales [11]. Annual ryegrass is typically managed in Australian cereal crops using multiple cultural practices including chemical control, early sowing, higher seeding density, timely post-harvest grazing, and occasional tillage [11], plus the strategic use of competitive crops and pasture species [12][13][14], and most recently, by the reduction of viable seeds through harvest weed seed destruction using chaff-lining [15] and weed seed destructors [16].…”
Section: Introductionmentioning
confidence: 99%